2012
DOI: 10.1039/c2nr30379e
|View full text |Cite
|
Sign up to set email alerts
|

Surface-structure-regulated penetration of nanoparticles across a cell membrane

Abstract: The cell uptake rate of nanoparticles (NPs) coated with mixed hydrophilic/hydrophobic ligands is known to be strongly influenced by the ligand pattern on the nanoparticle surface. To help reveal the physical mechanism behind this intriguing phenomenon, here we perform dissipative particle dynamics simulations to analyze the evolution of free energy as the ligand-coated NPs pierce through a lipid bilayer. Four characteristic ligand patterns are considered: striated NPs with alternating hydrophilic and hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
185
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(193 citation statements)
references
References 67 publications
(76 reference statements)
5
185
1
2
Order By: Relevance
“…The similar free energy change induced by switching from random ligand structure to ordered ligand structure has been also reported by Gkeka et al (2013). Li et al (2012) conducted further analysis for understanding why the NP with striated ligand pattern exhibited the higher permeability. They indicated that the shallow energy minimum of the striated NP is attributed to lower degree of freedom for rotation of the striated NP in the hydrophobic region of the bilayer.…”
Section: Biased MD Simulation Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The similar free energy change induced by switching from random ligand structure to ordered ligand structure has been also reported by Gkeka et al (2013). Li et al (2012) conducted further analysis for understanding why the NP with striated ligand pattern exhibited the higher permeability. They indicated that the shallow energy minimum of the striated NP is attributed to lower degree of freedom for rotation of the striated NP in the hydrophobic region of the bilayer.…”
Section: Biased MD Simulation Studiesmentioning
confidence: 95%
“…This issue has been investigated by MD simulation studies. Li et al (2012) investigated the direct permeation of ligand-coated NPs with two different types of ligand structural patterns: striated pattern with orderly arranged hydrophilic and hydrophobic domains ("St" in Fig. 4(a)), and randomly arranged pattern at the same ratio of the hydrophilic and hydrophobic ligands ("Rand" in Fig.…”
Section: Biased MD Simulation Studiesmentioning
confidence: 99%
“…When the ligands were arranged as stripes, the particles were able to translocate easily across the membrane, while in the random arrangement endocytosis occurred. [147][148][149] Endocytosis serves to absorb molecules from the extracellular space by invagination of the plasma membrane and formation of intracellular vesicles. The first type of endocytosis discovered was clathrin-mediated endocytosis, but in the meantime several additional types of endocytosis have been identified.…”
Section: Mechanisms Of Cellular Entrymentioning
confidence: 99%
“…Studies have found that peptide encapsulated fluorescent silver nanoclusters [49] and polyarginineconjugated iron oxide NMs loaded with siRNA can directly penetrate cell mebranes [55]. Similar to CPPs, several synthetic NMs, such as synthetic amphipathic phospho lipid polymers [56] and nanoparticles (NPs) coated with hydrophilic-hydrophobic striated ligand shell [57,58] can also penetrate the mem brane in a similar manner to the CPPs without disrupting the membrane. Table 1 summarizes the cellular uptake path ways of different NMs.…”
Section: Future Science Groupmentioning
confidence: 99%